THE INFLUENCE OF THE HUMAN DEVELOPMENT INDEX INDICATOR ON ECONOMIC GROWTH IN IN KEDIRI REGENCY - Jati, Bayu Anggoro; Iriani, Ririt (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTHuman development is an important indicator of a country's economy. The high quality of human beings can encourage the economy in a region to move in a better direction. Although the level of human development increases every year from 2010 to 2021, this has not been able to pump up economic growth in Kediri Regency. This study aims to determine the effect of the health index, education index, and purchasing power index on economic growth in the Kediri Regency. The data used is secondary data obtained from the Central Bureau of Statistics of Kediri Regency. The analytical method used is the multiple linear regression analysis methods. Based on the results of data processing, it was found that the health index, education index, and public purchasing power index had a simultaneous and significant effect on economic growth in Kediri Regency, while the partial test results showed that the education index and public purchasing power index had a positive and significant effect on economic growth, while the health has no significant effect on the economic growth of Kediri Regency. The positive relationship that occurs between human development and economic growth proves that the policy of equitable distribution of human development needs to be an important concern for the government.Keywords: Human Development Index, Economic Growth